PENERAPAN PERMAINAN LINGKARAN WARNA BERBASIS TEORI PIAGET UNTUK MENINGKATKAN PERKEMBANGAN MOTORIK KASAR USIA 5-6 TAHUN - qonita (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2026)
The main purpose of this research is to improve the gross motor development of 5-6 year old children through the application of color circle games based on Piaget's theory. The descriptive qualitative approach with a case study method was used on one 5-year-old child who experienced gross motor delays in kindergarten. The intervention was carried out for three weeks, three times a week, focusing on color circle games involving jumping, balancing on a plank, throwing and catching a ball, frog jumps, and bear walks. The results showed significant development in the subject. The child became braver in jumping, showed improved balance and body control, better hand-eye coordination, and became more active and self-confident. This change proves that the obstacle course game based on Piaget's theory is an effective medium for stimulating children's gross motor skills, courage, and self-confidence.